Sex Differences in Cerebral Blood Flow and Serum Inflammatory Cytokines and Their Relationships in Mild Traumatic Brain Injury - Zhao, Pinghui; Zhu, Pingyi; Zhang, Danbin; Yin, Bo; Wang, Yu; Hussein, Nimo Mohamed; Yan, Zhihan; Liu, Xiaozheng; Bai, Guanghui (Frontiers in Neurology, 2022)
This study aimed to investigate sex differences in cerebral blood flow (CBF) and serum inflammatory cytokines, as well as their correlations in patients with acute-stage mild traumatic brain injury (mTBI). Forty-one patients with mTBI and 23 matched healthy controls underwent 3D-pseudo-continuous arterial spin labeling imaging on 3T magnetic resonance imaging. The patients underwent cognitive evaluations and measurement of a panel of ten serum cytokines: interleukin (IL)-1I, IL-4, IL-6, IL-8, IL-10, IL-12, C–C motif chemokine ligand 2, interferon-gamma, nerve growth factor-beta (β-NGF), and tumor necrosis factor-alpha (TNF-α). Spearman rank correlation analysis was performed to evaluate the relationship between inflammation levels and CBF. We found that both male and female patients showed increased IL-1L and IL-6 levels. Female patients also demonstrated overexpression of IL-8 and low expression of IL-4. As for CBF levels, three brain regions [the right superior frontal gyrus (SFG_R), left putamen, and right precuneus] increased in male patients while three brain regions [the right superior temporal gyrus (STG_R), left middle occipital gyrus, and right postcentral (PoCG_R)] decreased in female patients. Furthermore, the STG_R in female controls was positively correlated with β-NGF while the right PoCG_R in female patients was negatively correlated with IL-8. In addition, compared with male patients, female patients showed decreased CBF in the right pallidum, which was negatively correlated with IL-8. These findings revealed abnormal expression of serum inflammatory cytokines and CBF levels post-mTBI. Females may be more sensitive to inflammatory and CBF changes and thus more likely to get cognitive impairment. This may suggest the need to pay closer attention to the female mTBI group.